2012
DOI: 10.1016/j.jcrs.2012.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different femtosecond laser-firing patterns on collagen disruption during refractive lenticule extraction

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…All experimental eyes underwent a spherical −6.00D myopia correction. The femtosecond laser parameters used in this experiment were as described previously [22], [23]: 120 µm flap thickness, 7.5 mm flap diameter, 175 nJ power, and side cut angles at 90 degrees. The spot distance and tracking spacing were set at 3 µm/3 µm for lenticule, 2 µm/2 µm for lenticule border, 3 µm/3 µm for flap, and 2 µm/2 µm for flap side cut.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All experimental eyes underwent a spherical −6.00D myopia correction. The femtosecond laser parameters used in this experiment were as described previously [22], [23]: 120 µm flap thickness, 7.5 mm flap diameter, 175 nJ power, and side cut angles at 90 degrees. The spot distance and tracking spacing were set at 3 µm/3 µm for lenticule, 2 µm/2 µm for lenticule border, 3 µm/3 µm for flap, and 2 µm/2 µm for flap side cut.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical staining was performed as described previously [21][23]. The following primary antibodies and the corresponding working dilution factor were used: mouse monoclonal antibody against cellular fibronectin (Millipore, Billerica, MA) diluted 1∶400; tenascin-C (Abcam, Cambridge, UK) diluted 1∶200; collagen type I (Sigma) diluted 1∶100; and CD18 (Novus Biologicals, Littleton, CO) diluted 1∶100 in the blocking solution.…”
Section: Methodsmentioning
confidence: 99%
“…The femtosecond incisions were performed in a spiral in/out scanning pattern direction. 18 That is, first the posterior surface of the lenticule was cut (spiral in, centripetal direction), second the anterior surface of the lenticule and a cap extension were cut (spiral out, centrifugal), followed by the lenticule side cut and a small arcuate incision. The femtosecond laser parameters were: 200 nJ power, 110 lm cap thickness, 7.5 mm cap diameter, 6.5 mm lenticule diameter, and minimum and maximum lenticule thicknesses of 15 and 105 lm, respectively.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Especially, nonlinear phenomena such as self-focusing depend critically on actual tissue properties and focusing conditions [36,38]. Furthermore, a recent study has shown that there is a difference in visual outcome between laser patterns which are centrifugally or centripetally applied [39]. This difference is explained by the deformation of the corneal tissue during laser treatment, which is also not described by the solid CL material of our eye model.…”
Section: Discussionmentioning
confidence: 99%